Exploring school counselors’ preparation to address disproportionality of African American students in special education - E Mackenzie Shell (Teaching and Supervision in Counseling, 2020)
While school counselors work with students in special education, little research describes their work with African American students in or at risk of special education or the phenomenon of disproportionality of African American students in special education. This phenomenological study explored the experiences and perceptions of eight high school counselors with African American students in special education and disproportionality. The researcher identified three themes: (a) Dis-Regard, (b) separate worlds and (c) professional knowledge. Intentional strategies to introduce counselors to the concept of disproportionality and its antecedents may mitigate processes that potentially lead to overrepresentation of African Americans in special education.
Keywords: school counselors; disproportionality; overrepresentation; special education; counselor education